Genome polymorphism and alcoholism - Thome, Johannes; Gewirtz, Jonathan C; Weijers, Heinz-Gerd; Wiesbeck, Gerhard A.; Henn, Fritz A. (Pharmacogenomics, 2004)
Different gene variants have been identified as risk or protective factors in alcoholism. The genes coding for dopamine receptors, serotonin transporters, and dehydrogenases represent susceptibility loci for addictive behaviour. However, alcoholism represents a complex psychiatric symptomatology which is caused by multiple factors, both genetic and environmental. Furthermore, there are probably different subtypes of alcoholism each with a distinct pathophysiology, and thus a different genetic background. Genetic research can help to identify such subtypes, which may require different therapeutic approaches. However, gene polymorphisms are not only responsible for a predisposition to alcoholism, but also for personality traits which influence the likelihood of developing addictive behaviour. Moreover, genetic polymorphisms are probably involved in the way an individual responds to treatment. Also, the severity of secondary diseases resulting from chronic alcohol uptake may depend on the genetic makeup of an individual. New treatment strategies focusing on genes contributing towards drug and alcohol dependence (such as gene therapy) are already under examination in animal models. However, further research is required before these developments will considerably change today’s clinical handling of alcoholism.